Interference mitigation in downlink co-tier network using dynamic power control / Fatin Liyana Ahmad Padzi - Ahmad Padzi, Fatin Liyana (2014)
Recently femtocellsis seem to bethe most promising solution to the indoor wireless internet users. However, the extend number of user has led to increase the capacity demand for packet-based mobile broadband system. Due to the scarcity of the spectrum resources, has contributed femtocells to share spectrum with other networks, which inevitably bring in severe interference. Therefore, this paper is proposing a dynamic power control in order to mitigate the interference level in thedownlink co-tier networks, hence the good QoScan be served.